Cercospora Leaf Spot Disease of Castor in Ericulutre: A Review on Existing Management Strategies - , P.R. Narzary; , A. Das; , D. Brahma; , R. Verma; , M. Saikia; , P. K. Kaman; , J. Sarma (Archives of Current Research International, 2024)
The deadly illness known as "Cercospora leaf spot of castor" affects castor (Ricinus communis L.) plants, which serve as the main food supply for the eri silkworm (Samia ricini Donovan). It is brought on by the fungal infection Cercospora ricinella. The growth and development of eri silkworms as well as the production of silk may be negatively impacted by this disease, which can result in large losses in leaf output, quantity, and quality. This article covers a range of environmentally friendly methods for controlling Cercospora leaf spot in castor plants. It also looks at the effects of chemical fungicides on silkworms and the possibilities of integrated approaches to disease control. By adopting eco-friendly and sustainable methods, the ericulture industry can effectively combat this disease while ensuring the safety and well-being of the eri silkworms and the environment.